Assessment of Cancer Patient's Satisfaction Regarding Nurses Communication Skills in Azadi Teaching Hospital/ Oncology unit - Dia'a AL-Rahman Abdullah; Radhwan Hussien Ibrahim (College of Nursing,University of Mosul, 2016)
Background and aim: Communication is the process of transmitting thoughts, feelings, facts, and other information, includes verbal and nonverbal behavior. Communication is an essential element of the nurse-client relationship, teaching of client, and entire activities performed by nurses. To be an effective communicator, the nurse must be aware of the different levels on which communication is conducted between nurses and clients and among members of the health care team. Applying the aspects of communication level helps the nurse establish a therapeutic relationship with the client and thereby achieve successful outcomes of care. The study aims to assess Cancer Patient's Satisfaction Regarding Nurses Communication Skills in Azadi Teaching Hospital as well as to find out the relationship between Patient's Satisfaction and some Socio- demographic characteristic such as age, gender and level of education. Materials and method: A descriptive study of a quantitative design was carried out at oncology unit in Azadi teaching hospital in Kirkuk city for cancer patients from 1st of December, 2015, up to the 16th of February, 2016. A non-probability (convenience) sample of (120) definitely diagnosed with cancer disease. Selected from patients who were attended to Azadi teaching hospital generally for receiving chemotherapy dosage. Developed questionnaire was constructed for the purpose of the study which consisted of three parts: the demographic data of the respondent, the nature nurse-client relationship, and satisfaction regarding therapeutic communication. The data were collected through the use of interview with the patients. They were analyzed through the application of descriptive statistical analysis and inferential statistical data analysis. Results: The findings of the study indicated that (24.2%) of the samples were in age group (50-59) years and (≥60) years, (51.7%) of them were male, (32.5%) of the sample were illiterate, (40.0%) of them were housewife, (87.5%) of the sample were married, (79.2%) of the sample were urban residency, (23.3%) of the sample had have breast cancer, and (70.8%) of the sample were staying ≤ 1 day in the hospital. Conclusions: the study concluded that most of the patients were dissatisfied regarding the nature of Nurse-Patient communication. Most of patients were satisfied regarding Therapeutic communication. RECOMMENDATIONS The present study recommends that trained educational program should be designed to increase nurses' awareness and knowledge about modes of communication. Keywords: cancer patients, communication skills, satisfaction.